Drivers of consumers’ intention to adopt sustainable healthy dietary patterns: evidence from China - Chen, Xiujuan; Jiang, Xue; Wu, Linhai (Frontiers in Sustainable Food Systems, 2024)
Introduction In line with the shift towards sustainable consumption, sustainable healthy dietary patterns (SHDP) have received considerable attention, but no study has examined Chinese consumers’ intention to adopt SHDP. Methods Based on the theory of planned behaviour (TPB), this study integrated health consciousness, environmental concerns, and past eating behaviour to construct an expanded TPB framework for analyzing the factors influencing Chinese consumers’ intention to adopt SHDP. The mediating role of attitude between perceived value and consumers’ intention to adopt SHDP was also analyzed. The study empirically tested the research model using structural equation modelling estimation, based on the data collected from 402 local consumers in Wuxi, China. Results and discussion The results showed that attitude, perceived behavioural control, health consciousness, and past eating behaviuor positively and significantly influenced consumers’ intention to adopt SHDP, whereas perceived value indirectly influenced adoption intention through attitude. Subjective norms and environmental concerns had no significant influence on adoption intention. Based on these findings, interventions through dietary education and information campaigns are recommended to enhance consumers’ value awareness and attitudes towards SHDP. Interventions, such as nudging, should be designed to enhance consumers’ perceived behavioural control and dietary practises. The findings of this study provide important insights for the development of dietary change intervention strategies.